Primary Healthcare Providers' Knowledge on the Early Detection of Biliary Atresia - Prihaningtyas, Rendi Aji; Setyoboedi, Bagus; Nesa, Ni Nyoman Metriani; Masturina, Melinda; Utomo, Martono Tri; Arief, Sjamsul (Folia Medica Indonesiana, 2024)
Highlights: 1. An evaluation is necessary to verify that the knowledge of healthcare providers is sufficient for the early detection of biliary atresia. 2. It is crucial to promote education on prolonged jaundice to ensure early detection of biliary atresia in primary health facilities, as some primary healthcare providers have insufficient knowledge on the subject. Abstract Primary healthcare providers frequently fail to recognize biliary atresia because it closely mimics physiological jaundice. Early detection plays an important role in ensuring the optimal treatment of biliary atresia. Delays in referring to biliary atresia cases remain a problem around the world. The objective of this study was to analyze the knowledge of primary healthcare providers regarding prolonged jaundice as an early sign of biliary atresia. A cross-sectional study was conducted at primary healthcare centers using a self-administered questionnaire. The data were analyzed descriptively with the assistance of IBM SPSS Statistics for Windows, version 21.0 (IBM Corp., Armonk, N.Y., USA). A total of 271 respondents participated in this study, including midwives (63.8%), nurses (24.4%), and medical doctors (8.5%). This study found that 73.8% of the respondents agreed that infants with prolonged jaundice need to undergo a serum bilirubin level assessment. However, 40.2% of the respondents believed that pale stools and dark urine in yellow infants were symptoms of physiological jaundice. Concerning the definition of prolonged jaundice, 209 (77.1%) respondents provided a response indicating more than two weeks. A total of 137 (50.6%) respondents stated that biliary atresia is a disease that must be ruled out first in cases of prolonged jaundice. Nevertheless, 86 (31.7%) and 87 (32.1%) respondents also mentioned that breastfeeding jaundice and breast milk jaundice must be considered as potential causes to be investigated. These results indicated that primary healthcare providers still had limited knowledge regarding cholestasis. Education on prolonged jaundice in primary healthcare centers should be more improved to enhance the early detection of biliary atresia.